Efficacy and safety of novel digital single-operator peroral cholangioscopy-guided laser lithotripsy for complicated biliary stones - Wong, John CT; Tang, Raymond SY; Teoh, Anthony YB; Sung, Joseph JY; Lau, James YW (Endoscopy International Open, 2017)
Background/study aims Laser lithotripsy can effectively fragment complicated biliary stones, but current cholangioscopes are limited by fragility, restricted mobility or moderate visual resolution. The efficacy and safety of a new digital single-operator peroral cholangioscope to guide laser lithotripsy were evaluated. Patients and methods In this prospective single-center series, consecutive patients with complicated biliary stones, defined as impacted stones > 1.5 cm in size and wider than the more distal common bile duct, or stones that failed extraction by basket mechanical lithotripsy, underwent ERCP and SpyGlass DS peroral cholangioscope (Boston Scientific, Marlborough, United States)-guided laser lithotripsy. Stone clearance rate and incidence of adverse events were determined. Results Seventeen patients (10 men, 7 women; median age 76 years) with a median biliary stone size of 2 cm underwent predominantly holmium:yttrium aluminum garnet laser lithotripsy, achieving a 94 % stone clearance rate over 1 median procedure. Lithotripsy was performed in 8 of 17 patients due to an impacted biliary stone. The remaining patients underwent lithotripsy due to prior failure of the basket mechanical lithotripter to capture or crush their stones. Post lithotripsy, 2 patients developed cholangitis and 1 patient with underlying COPD developed respiratory distress, all resolved with conservative management. There were no hemobilia, perforations, pancreatitis nor any deaths. Conclusion SpyGlass DS peroral cholangioscopy-guided laser lithotripsy is an efficient and safe modality for management of complicated biliary stones.